Spectrophotometric determination of Valsartan in pure form and in its pharmaceutical preparations - Rashid, Qabas; Ruwaida Farman Salih (Al-Qadisiyah Journal of Pure Science, 2021)
An easy, rapid and economical spectrophotometric method for determination of Valsartan (Val), by reaction with 4-chloro-7-nitrobenzofurazan (NBD-Cl) as reagent in an alkaline interemediate. This method is based on the forming of product between (Val) and the chromogenic reagent (NBD-Cl), to produce a brown color at (pH 11.9) and λmax. 470 nm. Beer’s Law is obeyed at the concentrations range of (0.4-14.8 µg/ml), with molar absorptivity of (1.05×104 L/mol.cm) and correlation coefficient 0.9827, The limit of detection was 0.557 µg/ml. The suggested method was prosperity implement to the determination of (Val) in pure form and in its pharmaceutical formulations (tablets).